1989
DOI: 10.1038/338357a0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution (1.5 Å) crystal structure of phospholipase C from Bacillus cereus

Abstract: Both the phosphatidylinositol-hydrolysing and the phosphatidylcholine-hydrolysing phospholipases C have been implicated in the generation of second messengers in mammalian cells. The phosphatidylcholine-hydrolysing phospholipase C (PLC) from Bacillus cereus, a monomeric protein containing 245 amino-acid residues, is similar to some of the corresponding mammalian proteins. This, together with the fact that the bacterial enzyme can mimic the action of mammalian PLC in causing, for example, enhanced prostaglandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
264
2
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(279 citation statements)
references
References 35 publications
9
264
2
4
Order By: Relevance
“…Ca 2ϩ is required for the interaction of the toxin with membranes, whereas Zn 2ϩ plays a structural role. Crystallographic studies have revealed that the B. cereus PC-PLC has two tightly bound and one loosely bound Zn 2ϩ ions, which are required for the enzymatic activity (48). These Zn 2ϩ ions are coordinated to several residues conserved in the C. perfringens PLC, which suggests that these two enzymes have the same catalytic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ is required for the interaction of the toxin with membranes, whereas Zn 2ϩ plays a structural role. Crystallographic studies have revealed that the B. cereus PC-PLC has two tightly bound and one loosely bound Zn 2ϩ ions, which are required for the enzymatic activity (48). These Zn 2ϩ ions are coordinated to several residues conserved in the C. perfringens PLC, which suggests that these two enzymes have the same catalytic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, this closed shell configuration causes problems for the (bio)chemist studying Zn(II) systems as this configuration is spectroscopically silent. The problem is often solved by replacing, in vitro, Zn(II) with Co(II) or Cu(II) and utilising the excellent spectroscopic properties of these ions, 109 or with Cd(II) and using 113 Cd-NMR spectroscopy as a probe. 110 In addition to dinuclear Zn(II) hydrolases, mono-and trinuclear enzymes are also common in nature.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 99%
“…80 The natural abundance of 113 Cd is 12.22% 153 and it is very sensitive to environment changes due to the large surrounding electron cloud. It is also a spin 1/2 nucleus which generally yields sharp NMR signals, making 113 Cd NMR spectroscopy a useful method for structure elucidation in biological, inorganic and organometallic cadmiumcontaining samples. 110,154 Cd(II) is known to be extremely toxic to mammals, hence it is generally viewed as an element that is not used by nature.…”
Section: Dinuclear Cadmium Hydrolase Mimicsmentioning
confidence: 99%
“…and examples of hydrolytically active zinc enzymes include P1 nuclease, [10] alkaline phosphatase, [11] phospholipase C, [12] and aminopeptidase. [13] The catalytic role of zinc in these enzymes includes Lewis acid activation of the substrate and the formation of Zn-OH which can act as an efficient nucleophile or as a general base catalyst at physiological pH.…”
Section: Phosphate (Hpnp) a Detailed Kinetic Analysis Suggested Thatmentioning
confidence: 99%